Thailand's urbanized villagers and political polarization. Issue 3 (3rd July 2017) - McCargo, Duncan
ABSTRACT: Thailand currently suffers from high levels of political polarization; parties associated with former Prime Minister Thaksin Shinawatra have won every election since 2001, based partly on strong support from voters registered in the populous North and Northeast regions. Many of these voters are migrant workers who spend much of their time working in Greater Bangkok, yet remain legal residents of their home provinces. This article argues that Thailand's political polarization could be reduced if many of these "urbanized villagers" either took up formal residence in the capital city, or were encouraged to share in the creation of new small-scale urban communities in their places of birth.